(untitled) (Archaeologia Adriatica, 2008)
The Nymphs (Greek Νύμφαι, Latin Nymphae) were the Greek and Roman goddesses of water, woods, and forests. They were the daughters of various parents, often unknown, and in the hierarchy of the gods they occupied a lower position, and many were not even immortal. At the end of November 2006, rescue excavations were carried out in the southern wing of the monastery of St. Nicholas in Zadar. The most interesting finds were two sculptures of the Nymphs, both made of Greek marble. The first sculpture depicts a female standing figure supported by the jug in her bent left arm, which was attached to a stylized depiction of a rock from which water ran. She is depicted frontally, with the left leg slightly forward (contrapost). The weight of the body is on the right leg, while the left is bent at the knee in a step. She is clothed in a long pleated tunic (chiton), which because of her posture slides slightly off the right shoulder. The finely made drapery depicted a thin dress. The head is missing (the remains of holes for placing the head can be seen), as well as the right hand (where remains can be seen of an iron spike for attaching the hand), and a smaller part of the left hand. Neither the feet nor the base on which the figure took were preserved (most often the Nymphs were depicted barefoot). The rear part of the sculpture was less carefully worked. The second sculpture depicts a free standing female figurine clothed in a long pleated dress (chiton), with finely made drapery. She is depicted slightly inclined to the left, which caused the chiton to slip off the left shoulder and expose the left breast. The weight of the body rests on the right leg, while the left leg is bent at the knee and raised, as if it supports a jug of water. The head is missing (the remains of holes for fastening the head can be seen), as well as both hands. The circular base on which the figure rested has been partially preserved, as has the right bare foot. The rear part of the sculpture was less carefully worked. The sculpture most probably belonged to a small nympheum or fountain of a Roman urban mansion (domus urbana). A reclining figure of a Nymph from the end of the 1st or early 2nd centuries AD was discovered in the archaeological excavations of the Roman forum in Zadar. It was discovered next to the nympheum, used secondarily as a cover for the city drains. The Archaeological Museum in Zadar contains another somewhat preserved sculpture of a Nymph, unfortunately without any data about the site of discovery. It belongs to the iconographic type of a Nymph with shells, with the upper part of the body nude and a mantle sliding down the flanks. All four statues of Nymphs discussed in this article can be dated to approximately the same time, the end of the 1st century or in the 2nd century AD. These four Nymphs were related to water (Nymphae fontanae). These would thus be Naiads, nymphs of springs who were worshipped as the personification of forces ruling over sources of water, as those who return health and power to the body (salutares). The construction of a nympheum or fountain in Iader, whether for public or private purposes, could be related to one of the city wells of fresh water. An entire series of Roman public and private wells with fresh water have been established in the area of the Zadar peninsula. As yet there is no epigraphic testimony for a cult of the Nymphae in Iader. .